Informed Employees - Informed Consent as Ethical Guidance for Behavioural Prevention in the Corporate Context Aufgeklärte Mitarbeiter/innen - Die informierte Einwilligung als ethische Orientierung für Verhaltensprävention im betrieblichen Kontext - Kuhn, Eva; Mueller, Sebastian; Heidbrink, Ludger; Buyx, Alena (Gesundheitswesen, 2021)
Background and Method People have a right to physical and mental integrity in all spheres of life. They also have the right to autonomous actions and informed decisions regarding their health. To ensure this, informed consent has been the ethico-legal gold standard in medicine for some years now. The registration for measures of behavioural prevention, in contrast, is mainly conducted through forms focussing on data protection, with little attention to full informed consent of future participants. In this article, we discuss the ethical challenges that arise when employees consent to health-promoting measures. We then examine whether the instrument of informed consent can be translated to the context of behavioural prevention. Results Informed consent can be transferred to the corporate context in an altered version. Of particular importance is not only the handling of health-related data, but also the appropriate disclosure of all essential information as well as voluntary participation. Conclusions The adjusted version of informed consent in behavioural prevention ought to be developed further, resulting in a matrix of criteria that define conditions under which the informed consent can be applied to single measures of behavioural prevention.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Corporate Responsibility; Health Promotion; Informed Consent; Medical Ethics; Workplace